Relationship between emotional intelligence and quality of healthcare among nurses - Oweidat, Islam; Alzoubi, Mahmoud; Shosha, Ghada Abu; Ta’an, Wafa’a; Khalifeh, Anas; Alzoubi, Majdi M.; Al-Mugheed, Khalid; Alabdullah, Amany Anwar Saeed; Abdelaliem, Sally Mohammed Farghaly (Frontiers in Psychology, 2024)
Introduction Healthcare organizations worldwide face intense competition for survival in an ever-changing environment. Objectives This study aims to examine the relationship between emotional intelligence (EI) and quality of healthcare (QHC) among Jordanian nurses working in governmental hospitals. Method This study was conducted using a descriptive correlational design and included a sample of 172 nurses. Participants from five governmental hospitals in Jordan completed online self-administered questionnaires, including the Nurse-Assessed Quality of Nursing Care Scale and the Genos Emotional Intelligence Concise Scale, along with sociodemographic data. Results The participating nurses demonstrated a high level of EI (M = 3.809, SD ± 0.484) and a very high level of QHC (M = 4.260, SD ± 0.372). A statistically significant correlation was found between the total quality of healthcare variables and the total EI variable (r = 0.739, p < 0.01). Additionally, statistically significant correlations were observed between the QHC and EI, as well as their respective dimensions (r = 0.357–0.739). EI was found to be a significant predictor of the QHC (F = 34.872, p ≤ 0.001), with a positive correlation between the two variables (r = 0.733). EI accounted for 59.8% of the variation in the QHC. Conclusion EI is a key predictor of QHC. It plays an essential role in recruiting, staffing, promoting, and nurturing employees, making it a crucial criterion for achieving excellence in healthcare organizations.